Analisis Yuridis Kapal kesehatan (Bantu Rumah Sakit) dalam Misi Kemanusiaan Masa Perang dan Damai - Susdarwono, Endro Tri (Hukum dan Masyarakat Madani, 2019)
Since a long time ago, BRS (Hospital Assistance) had played a major role in saving lives. Under the Hague Regulations of 1907, BRS type ships were prohibited from being attacked in warfare and these ships themselves were prohibited from possessing weapons. Indeed, World War I and II experience shows that BRS ships remain the target of attacks. It was only after World War II was over, this immunity could be implemented in the field. The Republic of Indonesia is a participant of the Geneva Conventions of 1949 concerning Protection of War Victims by means of a declaration of participation dated 10 September 1958, based on Law Number 59 of 1958 concerning the participation of the Republic of Indonesia in all Geneva Conventions on 12 August 1949 (Lembaran Negara No. 109, 1958. BRS operates not only during wartime, but also during peacetime, BRS operations in peacetime in the form of disaster relief and ordinary situations. In ordinary situations, BRS visits remote islands to provide medical assistance and equipment free medical services for the local community